Review of the brachypterous species of the genus Dichotomius Hope (Coleoptera: Scarabaeidae: Scarabaeinae) - Nunes, Rafael Vieira (2012)
The genus Dichotomius Hope (Coleoptera, Scarabaeidae, Scarabaeinae) comprises about 170 species endemic to the Americas mainly distributed in the tropics, and divided in four subgenera: Dichotomius Hope, Selenocopris Burmeister, Homocanthonides Luederwaldt and Luederwaldtinia Martinez. Some species of this genus are brachypterous, which means they have atrophy on the hind (or membranous) wing, therefore, they are flightless. This character is found on three subgenera of Dichotomius what makes the brachypterous Dichotomius an artificial group. We had three main aims in this dissertation: 1) to do a taxonomic review of the brachypterous species of the genus Dichotomius; 2) to discuss evolutionary aspects of the brachypterism in the genus and 3) to access conservation status of the brachypterous species of the genus. There are nine described or new species of brachypterous Dichotomius: Dichotomius (D.) comarapensis Génier, placed in a homonymous complex; Dichotomius (S.) ingens (Luederwaldt), Dichotomius (S.) sp.5 n. sp., Dichotomius (S.) sp.3 n. sp., Dichotomius (S.) sp.4 n. sp., Dichotomius (S.) sp.2 n. sp., these last five species positioned in ascanius complex; Dichotomius (L.) eucranioides Pereira and D’Andretta, positioned in a homonymous complex, Dichotomius (L.) mysticus (Luederwaldt) positioned into geminatus complex and Dichotomoius (L.) sp.1 n. sp. placed in the batesi complex. We believe that brachypterism evolved independently at least five times in the genus, but there is the necessity of a phylogenetic analysis to test this hypothesis. Among brachypterous species of the genus, according to the criteria of IUCN, D. periotoi and D. mysticus can be considered Critically Endangered (CR) while the occurrence of the species is classified as Endangered (EN), Vulnerable (VU), Near Threatened (NT) and Data Deficient (DD). Population monitoring and respect to the specific environmental legislation need to be prioritized in order to conserve conserve the populations of the former species. In the conclusion chapter, a key for the brachypterous species of the genus Dichotomius and Holocephalus is provided.